Β-Mn formation and aging effect on the fracture behavior of high-Mn low-density steels. (November 2016) - Lee, Keunho; Park, Seong-Jun; Moon, Joonoh; Kang, Jun-Yun; Lee, Tae-Ho; Han, Heung Nam
Abstract: The β-Mn formation behavior of high-Mn low-density steels was investigated in terms of the morphological characteristics and alloying element distribution after aging treatments. A dramatic difference in the formation kinetics and morphology of β-Mn was observed depending on the addition of Al, which may increase the driving force for β-Mn formation. In addition, the effects of the aging process on the fracture behavior were examined in uniaxial tensile tests combined with microstructural observations. A severe loss of ductility resulted from the β-Mn formation and ordering of ferrite into the D03 phase, which was transformed before the β-Mn formation process.